A topical structure analysis to create coherence in English essays of fourth year students at English Department at Vietnam National University, University of Language and International Studies - Nguyễn, Thị Hồng (ĐHNN, 2017)
The present paper sets out to investigate English essays of Vietnamese learners using the Topical structure analysis (TSA) developed by Lautamatii (1978). In the population of forty essays written by forth year students at ULIS, VNU, twenty-six essays including thirteen high-rated and thirteen low-rated ones were taken out for two objectives. The first objective is to compare and contrast the physical features of two groups and the topical structures. The second objective is to establish a possible relationship between the essay holistic evaluation and the type of topical progressions used. Data analysis has revealed the moderately physical differences between two groups in terms of t-units, topical depths, but no significant difference could be found in the numbers of paragraphs and topical structures. In addition, findings also indicated that there was significant difference in the progression proportions used in two groups, especially in parallel progression in body paragraph and the subtypes of sequential progression in introductions and conclusions.